The Effect of Giving Caring Learning Topics to Student Caring Behavior in the Implementation of Nursing Practice in Dr.M. Haulussy Hospital - Hernita Frisnawati Purba (MOLUCCAS HEALTH JOURNAL, 2022)
Caring is the foundation in nursing practice. Nursing greatly affects the quality of health services, even being one of the determinants of the image of health care institutions (hospitals) in the eyes of the community. The emphasis on humanistic, caring, trust, commitment to helping others and various other caring elements must have been built since the nurse during the education period. The role of educational institutions is very important to pay attention to and improve the caring behavior of nursing students through the development of a model of caring swanson behavior based on emotional intelligence. Based on this, it is necessary to research the effectiveness of providing caring learning to students of Rumkit Tk III Nursing Academy to the caring behavior of students in undergoing nursing practice in hospitals. The purpose of this study is to identify the influence of caring learning topics on the caring behavior of students in undergoing nursing clinic practice.This study uses the design of quasi experiment pretest and posttest without a control group by intervening in the provision of caring learning topics to students of Rumkit Tk III Nursing Academy who are practicing at dr.M. Haulussy Ambon Hospital. The number of samples involved as many as 13 respondents who practiced in 3 inpatient rooms, namely the Pulmonary Chamber, Surgical Room and Interna Room.The results of the statistical test conducted, namely the Wilcoxon test, obtained the result p value = 0.001. (<0.05). This shows that there is an influence on the provision of learning materials with the topic of Caring on the caring behavior of students in undergoing nursing clinic practice, where all students experience an increase in caring behavior in running nursing clinic practices.